Morphology of the villous chorion maldevelopment in early forms of EPH-gestosis combined with anemia of pregnancy - N. M. Lagoda (Zaporozhye State Medical University, 2012)
On the basis of a complex morphological study of human placenta the characteristic structural features of villous maldevelopment in a combination of edema of pregnant and anemia of pregnancy are defined by the type of dissociated cotyledon development with retardation of the placental barrier functional specialization. This pathology leads to compensatory reactions of the placenta in the form of the restructuring of fetal blood vessels, aimed only at the oncoming of fetal and maternal blood flow without increasing of the vasculosyncytial membranes area. These changes were accompanied by complicated delivery and fetus state disorder characteristic for chronic feto-placental insufficiency, 2-nd degree of severity. Received results are the basis for inclusion of pregnant women with early form of EPH-gestosis (edema of pregnant) in combination with anemia into the risk group of fetoplacental insufficiency developing and complicated delivery.